Correction: Catalytic asymmetric hydrometallation of cyclobutenes with salicylaldehydes. Issue 4 (12th January 2022) - Goetzke, F. Wieland; Sidera, Mireia; Fletcher, Stephen P.
Abstract : Correction for 'Catalytic asymmetric hydrometallation of cyclobutenes with salicylaldehydes' by F. Wieland Goetzke et al., Chem. Sci., 2022, DOI: ; 10.1039/d1sc06035j .